2022
DOI: 10.2147/opth.s352503
|View full text |Cite
|
Sign up to set email alerts
|

Remote Imaging Capture with Widefield Swept-Source OCT Angiography During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has had a widespread impact on the health sector worldwide, both in the clinical and research subsector. This has necessitated for the invention of protocols compliant with social distancing policies to efficiently tackle the current needs. Our aim is to describe a novel remote imaging technique, which helped us continue our research with widefield swept-source optical coherence tomography angiography (WF SS-OCTA). Patients and Methods: As a part of this cross-sectional observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Social distancing measures led to innovation in research methods, tools and training methods and have been demonstrated in several studies (Bratan et al, 2021;Brito-Brito et al, 2022;Brog et al, 2022;Chasset et al, 2022;Garg et al, 2022;Greenough et al, 2022). Social distancing has acted as a catalyst for innovation and changes in research.…”
Section: Discussionmentioning
confidence: 99%
“…Social distancing measures led to innovation in research methods, tools and training methods and have been demonstrated in several studies (Bratan et al, 2021;Brito-Brito et al, 2022;Brog et al, 2022;Chasset et al, 2022;Garg et al, 2022;Greenough et al, 2022). Social distancing has acted as a catalyst for innovation and changes in research.…”
Section: Discussionmentioning
confidence: 99%